Pathfinding Solving in Maze Game Using Backtracking Algorithm - Tegar Arifin Prasetyo (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2023)
Games are a means of entertainment that great demand by the community. Besides games as entertainment, games can also practice thinking skills to find solutions. A game that contains elements of artificial intelligence requires algorithms in its implementation. One type of the game is Maze Game, where players are required to find a way out of the maze. Backtracking algorithm was chosen to solve this game. This algorithm works recursively to solve problems by finding possible solutions. If the path being traced is not the right solution, it will be backtracked and traced to other paths. This solution will not be ignored or deleted. But if the path taken is right, it will continue to check the next path until the player reaches the final solution.